TINDAK PIDANA PEMBUNUHAN DALAM HUKUM PIDANA ISLAM DAN HUKUM PIDANA POSITIF - Hifni, Mohammad; Hibar, Ujang; Agustiawan, M. Nassir (LPPM Universitas Bina Bangsa, 2023)
Islamic law is not prescribed for games and jokes. It is in accordance with the rules of the Shari'ah which fundamentally teach that the world is a place of testing and not eternal, while the Hereafter is a place of vengeance and eternal. Shari'ah also teaches that man is held accountable for his charity in the world and will be avenged in the Hereafter. The one who does good, the good will come back to him. If he does bad deeds, the ugliness will also come back to him. Therefore, punishment in the world will not remove punishment in the hereafter, unless he repents to God. The scholars of fiqh fatten down there are several punishments imposed on the perpetrators of this crime, namely: The original punishment, namely the law of qisas. This law is based on Allah's provisions in the Qur'an Surat Al Baqarah (2): 187) and (Q.S Al Maidah (5): 45) Substitute Punishment. According to fiqh scholars, if the punishment of qisas falls, for example forgiven or because there is peace, then there are two other substitute punishments, namely diyat borne by the murderer himself and the punishment of ta'zir. According to Imam al-Tahbrani, it is narrated from Amr bin Hazm Al-Anshari that the Prophet (peace be upon him) said: